The Quality of Peace in Post-Conflict Situation: A Comparative Study Between Armed Conflicts in Aceh and Bangsamoro - Latif, Ikhwan Rahmatika; Mutiarin, Dyah; Nurmandi, Achmad (UI Scholars Hub, 2020)
This article investigates the quality of peace in armed conflicts that occurred in the Southeast Asia region. The authors compared the cases of Aceh, where the armed conflict between the Free Aceh Movement or GAM and the government of Republic Indonesia ended peacefully with the Helsinki Memorandum of Understanding, with the conflict in the southern Philippines, where a peace agreement, the Comprehensive Agreement on the Bangsamoro, was successfully achieved between the government of Philippines and the Moro Islamic Liberation Front. This research employed document analysis to analyse the peace settlement documents of both parties and the derivative laws of the agreed settlements, as well as other relevant sources as the secondary data. All documents and sources were processed through the NVivo 12 application. The findings revealed that in both Aceh and Bangsamoro, the quality of peace is far from significant, for not all the terms of the agreements had been realised and there was still mutual suspicion prevailing between the two fighting parties. Therefore, what had been agreed upon in the Aceh and Bangsamoro post-conflict agreements must be accomplished as they should be in order to create a lasting peace, thereby allowing the people to experience a sufficient quality peace together.